Implementation of The Immersion Method in Arabic Language Learning at Madrasah Aliyah Cendekia Ruwaq Al-Azhar As-Syarif Pandan Duri, East Lombok - Nasirin, Nasirin; Nurdiah, Nurdiah; Nasri, Ulyan (Jurnal Ilmiah Profesi Pendidikan, 2023)
Arabic language education plays a crucial role in fostering a deep understanding of religious texts and Arab culture. Madrasah Aliyah Cendekia Ruwaq Al-Azhar As-Syarif Pandan Duri in East Lombok has implemented the immersion method to enhance students' Arabic language skills. This study aims to evaluate the effectiveness of the immersion method in Arabic language learning at the madrasah. The research method used is descriptive qualitative. Data were collected through observations, in-depth interviews, and questionnaires distributed to students and teachers. Data analysis techniques involved data collection, reduction, presentation, and conclusion drawing. The results of the study indicate that the immersion method significantly improves students' speaking and listening comprehension skills in Arabic. Students become more actively engaged in teaching and learning activities and show increased confidence in using Arabic in daily interactions. In conclusion, the implementation of the immersion method at Madrasah Aliyah Cendekia Ruwaq Al-Azhar As-Syarif is effective in enhancing students' Arabic language proficiency. The implementation of this research suggests the need for further development of immersion programs with the support of technology and more varied teaching materials to sustain the quality improvement of Arabic language learning.